WHY DO CHILDREN OF MIGRANT WORKERS TEND TO HAVE LEARNING DIFFICULTIES - Arif widodo; Umar (Jurnal Scientia, 2022)
Preliminary studies show that elementary school students who come from migrant worker families tend to have learning difficulties. Based on this phenomenon, researchers feel challenged to dig deeper into the phenomenon. This study aims to find out what forms of learning difficulties are experienced by students and the factors that cause them. The type of research used is a case study. The study was conducted in six public and private elementary schools in North Batukliang sub-district, Central Lombok regency. Data were collected through observation and in-depth interviews. Informants in this study were principals, teachers, and student caregivers. The results of the study found that on average the children of migrant workers experienced cognitive difficulties and behavioral disturbances. The forms of learning difficulties experienced include difficulty in reading and writing (basic literacy skills), and difficulties in arithmetic operations and number recognition (basic numeracy skills). Several factors are suspected to be the cause of student learning difficulties, including lack of tutoring from parents, low student motivation, constrained behavior disorders, low learning culture of students' social environment, and limited learning facilities owned by students.